2013
DOI: 10.1093/nar/gkt776
|View full text |Cite
|
Sign up to set email alerts
|

A novel route to product specificity in the Suv4-20 family of histone H4K20 methyltransferases

Abstract: The delivery of site-specific post-translational modifications to histones generates an epigenetic regulatory network that directs fundamental DNA-mediated processes and governs key stages in development. Methylation of histone H4 lysine-20 has been implicated in DNA repair, transcriptional silencing, genomic stability and regulation of replication. We present the structure of the histone H4K20 methyltransferase Suv4-20h2 in complex with its histone H4 peptide substrate and S-adenosyl methionine cofactor. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
53
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 48 publications
(69 reference statements)
16
53
2
Order By: Relevance
“…2B), indicating that, in vivo, in the embryo, the catalytic activity toward H4K20me3 is higher for SUV4-20H2 than for SUV4-20H1. This is in agreement with previous suggestions from crystallography work (Southall et al 2014). The low histone methyltransferase activity of SUV4-20H1 was lost upon mutating the NHDC sequence of its SET domain into AAAG, similar to SUV4-20H2 (Fig.…”
Section: The Developmental Failure Elicited By H4k20me3 Is Mediated Bsupporting
confidence: 92%
“…2B), indicating that, in vivo, in the embryo, the catalytic activity toward H4K20me3 is higher for SUV4-20H2 than for SUV4-20H1. This is in agreement with previous suggestions from crystallography work (Southall et al 2014). The low histone methyltransferase activity of SUV4-20H1 was lost upon mutating the NHDC sequence of its SET domain into AAAG, similar to SUV4-20H2 (Fig.…”
Section: The Developmental Failure Elicited By H4k20me3 Is Mediated Bsupporting
confidence: 92%
“…They comprise an N-terminal helical domain, the SET domain and a post-SET domain. Both structures are very similar and the SET and post-SET domains also share high similarity with other SET domain PKMTs [24,25]. The structure of SUV4-20H2 was also solved in complex with the substrate peptide showing several main chain contacts of the enzyme to the peptide in addition to hydrophobic contacts to R18, V21, L22 and hydrogen bonding to the side chain of D24 [25].…”
Section: Introductionmentioning
confidence: 90%
“…It is worth noting that both Suv4-20h1 and Suv4-20h2 are capable of monomethylation but with a 3-fold lower activity compared with their activity on mono-methylated peptides and a 250-fold lower activity relative to SETD8. The molecular basis for this specificity was revealed in structural studies on the SET domain of mouse SUV4-20H2, which showed that a single methyl group on the substrate lysine helps to lock the lysine in place in the active site (31,32). Peptides containing an unmodified lysine would therefore be oriented in a less optimal position rendering mono-methylation inefficient (31,32).…”
mentioning
confidence: 99%
“…The molecular basis for this specificity was revealed in structural studies on the SET domain of mouse SUV4-20H2, which showed that a single methyl group on the substrate lysine helps to lock the lysine in place in the active site (31,32). Peptides containing an unmodified lysine would therefore be oriented in a less optimal position rendering mono-methylation inefficient (31,32). With respect to tri-methylation, a significant structural rearrangement of the active site has to take place in order to accommodate an H4K20me3 peptide, which is energetically unfavorable, potentially explaining why this activity is difficult to detect in vitro when utilizing the SET domains of SUV4-20H1 and SUV4-20H2 (31,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation